Implementing Green Supply Chain Management in Paper Waste Management at Indonesian Higher Education Institutions: A Case Study of the Paper Recycling Ecosystem - Aisyah, Siti; Sentosa, Ilham; Ahmad Yahaya, Ahmad Naim (Technium Social Sciences Journal, 2024)
This study examines the implementation of Green Supply Chain Management (GSCM) practices in managing paper waste within Indonesian higher education institutions, focusing on the influence of recycling infrastructure, subjective norms, and recycling awareness on campus sustainability. Employing a quantitative approach with data from 224 students, the study utilized Structural Equation Modelling (SEM) to evaluate relationships among key variables: Paper Waste Capacity (PWC), Subjective Norms (SN), Recycling Awareness (RA), and Ecosystem Sustainability (ES). Findings indicate that enhanced paper waste capacity significantly affects subjective norms around recycling, while subjective norms positively influence individual recycling awareness. Both subjective norms and recycling awareness significantly contribute to ecosystem sustainability, suggesting that GSCM practices, supported by accessible recycling infrastructure and normative reinforcement, can foster a culture of sustainability within universities. This study also highlights the importance of creating a recycling-supportive environment through social campaigns and peer initiatives. The results underscore the broader potential of GSCM as a model for promoting environmentally responsible behaviours in educational settings and beyond. While limited by its specific context, the study calls for further research across diverse institutions and regions to expand understanding of GSCM's impact on sustainability practices